OPTIMALISASI PEMANFAATAN SARANA DAN PRASARANA DALAM MENDUKUNG PROSES PEMBELAJARAN MAHASISWA MPI UIN ALAUDDIN MAKASSAR - Yanti, Hilda; Ikhsan, Muh.; Firgiawan, Firdaus; Jufri, Apsarini (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the optimization of learning facilities and infrastructure in supporting the learning process of students in the Islamic Education Management (MPI) Study Program at UIN Alauddin Makassar. The research employed a qualitative approach with a case study design. The informants consisted of 16 MPI students, mostly from the 2024 cohort, selected purposively based on the intensity of their use of learning facilities. Data were collected through in-depth interviews, observations, and document analysis related to facilities and infrastructure management. The findings indicate that administratively, learning facilities and infrastructure have been managed through clear procedures; however, their utilization has not been fully optimized. The main constraints include inadequate whiteboards, poorly maintained air conditioning systems, technical issues with LCD projectors, and unstable Wi-Fi connectivity. Optimization efforts involve adaptive use of available facilities, strengthening regular maintenance, and active involvement of lecturers and students in maintaining and utilizing learning facilities. This study emphasizes that the optimization of facilities and infrastructure depends not only on availability but also on functionality and consistent management to enhance the quality of the learning process.